2019
DOI: 10.3390/app9102046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ultraviolet Aging on Adhesion Performance of Warm Mix Asphalt Based on the Surface Free Energy Theory

Abstract: To explore the effect of ultraviolet (UV) aging on the adhesion properties of warm mix asphalt (WMA), WMA binders were prepared by adding Evotherm M1 and Sasobit into base asphalt. The base asphalt and two WMA binders were aged using a self-made UV aging box after a rolling thin-film oven test (RTFOT). As a comparison, pressure aging vessel (PAV) tests were performed for asphalt binders after RTFOT. The contact angles between the WMA binder and distilled water, glycerol, and formamide, before and after UV agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Surface free energy refers to the work that a certain material does to create a new interface per unit area. The components of surface free energy are used to evaluate the adhesion between asphalt and aggregate ( 29 , 30 ), and the moisture damage resistance ( 31 ). Recently, AFM has been used to explore the surface microstructures, and topographical and mechanical (stiffness and adhesion) properties of asphalt binder ( 32 , 33 ).…”
mentioning
confidence: 99%
“…Surface free energy refers to the work that a certain material does to create a new interface per unit area. The components of surface free energy are used to evaluate the adhesion between asphalt and aggregate ( 29 , 30 ), and the moisture damage resistance ( 31 ). Recently, AFM has been used to explore the surface microstructures, and topographical and mechanical (stiffness and adhesion) properties of asphalt binder ( 32 , 33 ).…”
mentioning
confidence: 99%
“…Relevant studies have shown that UV light is the primary cause of the aging of asphalt pavement within the first four months after the pavement is laid [ 34 ]. Therefore, the indoor UV test in this paper simulated natural outdoor aging for four months.…”
Section: Methodsmentioning
confidence: 99%
“…The reason is some short-chain hydrocarbons will undergo addition and polymerization reactions to generate long-chain compounds in the aging process of SBSmodified asphalt binder, which will convert aromatic fractions and colloids into asphalt [24] . The asphalt content in asphalt is higher, which means smaller the surface free energy is, resulting in the hardening and crispiness of SBS-modified asphalt [25] . Finally, the interface strength of the composite specimen decreases significantly.…”
Section: Influence Of Interface Aging On the Interface Strengthmentioning
confidence: 99%